The economics of mental health - Richard Layard (IZA World of Labor, 2016)
In a typical country, one in five people suffers from a mental illness, the great majority from depression or crippling anxiety. Mental illness accounts for half of all illness up to age 45 in rich countries, making it the most prevalent disease among working-age people; it also accounts for close to half of disability benefits in many countries. Mentally ill people are less likely to be employed and, if employed, more likely to be out sick or working below par. If mentally ill people received treatment so that they had the same employment rate as the rest of the population, total employment would be 4% higher, adding many billions to national output.
Keywords: I18; 330; mental illness; psychological therapy; health; life-satisfaction